PENGETAHUAN GEJALA DEFISIENSI UNSUR HARA DAN PENANGANANYA SERTA KAITANNYA DALAM UPAYA MENCAPAI SISTEM PERTANIAN MODERN - Fakultas Pertanian UNISRI, Priyono (MAJALAH ILMIAH GEMA, 2003)
In relation to the deficiency of nutrients element (on the plant) in private is actuality a plant upset that we frequency observe, because if the needs of nutrient element are sufficient, so it is possible to maintain palnt’s health actually, if this effort is paid aatention rightly so it an efficient and economi cal effort, energy, time, and low risk effort , but the result is very principal to the planta growth and very beneficial in finance and food providing in the regions. In accordance with the advances in science and techonolgy so it is neces sary to handle the deficiency of nutrient elements accurately. The implementation of such handling needs the skilled man resources with sufficient menas are infrastructure. So if the activity could be realized of course, the effort to attain the modern farming system in the global era will be realized trhought the plantation development ariented by industrial an business agriculture Keywords: Knowledge, Elements Hara, Agricultural System Of Modern